Diagnosa Penyakit Kanker Paru-Paru Pada Perokok Aktif Menggunakan Metode Certainty Factor (CF) - Nana Elvana; Imran Lubis; Suci Ramadani (Bulletin of Multi-Disciplinary Science and Applied Technology, 2023)
Smoking habits or too often exposed to cigarette smoke are the main causes of lung cancer. Lung cancer is a primary malignant tumor of the lower respiratory system that is epithelial in nature and originates from the bronchial branching mucosa. the large number of active smokers is one of the causes of lung cancer. There are still many people who do not know about the early symptoms of lung cancer and are unsure whether it is lung cancer or other cancers. The lack of special facilities for lung cancer in Indonesia, which are still very limited, is another factor that causes the long process of treatment given to patients who may or do suffer from lung cancer. To be able to ensure a diagnosis of lung cancer or other diagnoses of diseases suffered, people with symptoms need to go to an expert or specialist in internal medicine for a consultation. However, experts who are not available, costs to consult with experts are also quite expensive and limited, which is another shortage factor. Based on the problems that occur, an expert system is needed that can store accurate information from an expert in diagnosing lung cancer in patients. The Certainty Factor method is a method that can be used in expert systems which is a combination of inference rules with a certain knowledge base given by one or more experts in a particular field. Certainty Factor uses a value to assume an expert's degree of confidence in a data. With the existence of an expert system, the public can consult without having to wait for the presence of a doctor. From the results of the trials conducted, it was found that the patient suffered from Non Small Call disease with a value of 98.53%.